The Effect of Irrigation Solution at Different Temperatures on Articular Cartilage Metabolism - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2011)
Purpose: The purpose of this study was to determine the effects of saline solution at different temperatures on the metabolism of chondrocytes. Methods: Porcine osteochondral explants were precultured under laboratory conditions. The cartilage explants were placed in saline solution. Twenty-four explants were randomly divided into 4 groups. Explants were immersed at 4 degrees C group I, at room temperature (24 degrees C) in group II, at normal knee temperature (32 degrees C) in group III, and at near-core body temperature (37 degrees C) in group IV. All specimens were immersed for 2 hours. Lactate and proteoglycan production and RNA yield analysis were performed to evaluate the changes in cartilage metabolism at different temperatures. Results: Explants immersed in cold (4 degrees C) saline solution showed the significantly lowest RNA yields, lactate production, and proteoglycan content. Explants immersed in cold solutions (4 degrees C and 24 degrees C) showed significantly lower RNA yields, lower lactate production, and lower proteoglycan content than explants in warmer solution groups (32 degrees C and 37 degrees C). Conclusion: The findings of this study suggest that short-term exposures to cold including room temperature may have markedly detrimental effects on chondrocyte function. Our findings also indicate that exposures to cold saline solution suppress chondrocyte metabolism and RNA synthesis. Clinical Relevance: Using warmer irrigation solution that is closer to body temperature is more physiologic and causes less ultrastructural damage than colder solution.
Keywords: INTRAARTICULAR TEMPERATURE; CHONDROCYTE; CRYOTHERAPY; ARTHROSCOPY; SURFACE